Opini Masyarakat Kota Medan Terhadap Pemilihan Serentak Presiden Dan Legislatif Tahun 2019 - Akhyar Anshori (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2019)
This study aims to determine the public opinion of the city of Medan against the simultaneous election of the president and legislators in 2019 using quantitative research methods. In determining the sample, the researcher used a probability sampling method, then the sampling technique was a proportional stratified sample. The sample size uses the Slovin formula about determining the number of samples from a particular population with a 5% error requirement. The subject of this study involved the people of Medan city who have been registered as permanent voters in the upcoming elections in 2019. This study uses correlational analysis of data analysis techniques. Correlational analysis is statistical analysis that seeks to find relationships or influences between two or more variables. The conclusion of this study found that around 95.25% of respondents knew that the 2019 elections would be held simultaneously while electing the president and legislature. And 77.50% of respondents agreed to the implementation of presidential and legislative elections carried out simultaneously. Keywords: Public Opinion, Elections, President and Legislature